Oral manifestations of leukemia as part of early diagnosis - Reyna Aguilar Quispe; Elizabeth Marques Aguiar; Claudia Teresa de Oliveira; Ana Cristina Xavier Neves; Paulo Sérgio da Silva Santos (Hematology, Transfusion and Cell Therapy, 2022)
Introduction: The oral cavity can present the first clinical manifestations of leukemia, therefore; it is important to recognize their principal characteristics. Objective: To identify oral manifestations as the first clinical signs of leukemia. Methods: This is an integrative review, that gathered data from articles with oral manifestations of leukemia as part of its first clinical features. The were included case reports, case series, clinical research, or reviews with case reports. The variables that were considered relevant: age, sex, sites of the oral lesions, characteristics of the oral lesions, medical history and physical examination, time of evolution, radiographic examination, blood test results, initial diagnosis, differential diagnosis and final diagnosis. Results: A total of 31 studies were included, with a total of 33 individuals identified. There were 19 (57.57%) males and 14 (42.42%) females. The age range was from 1.6 to 74 years. Acute myeloid leukemia (72.72%) and acute lymphoid leukemia (18.18%) presented more oral manifestations as the first clinical signs of the disease. All individuals with leukemia presented lesions, such as ulcer, erosion, bleeding, ecchymosis, color change of the bluish or pale mucous membranes and areas of tissue necrosis. Hard tissue lesions were less frequent, being 6 (18.18%). Conclusion: The first clinical manifestations of leukemia can be present in the oral cavity, mainly in acute myeloid leukemia. The principal oral tissues affected were gingival tissue, buccal mucosa and hard and/or soft palate. When hard tissues, such as the maxilla bone or mandible bone were affected, dental mobility was the principal clinical sign.